Cognitive Aspect of Translation Discourse - Andriyenko, Tetiana (East European Journal of Psycholinguistics, 2016)
The article is devoted to the study of translation as a special type of discourse which is understood as the process and the result of professional cognitive-communicative translator’s activity in the course of which a new cognitive entity is generated and embedded through language means – the concept of the target text. The cognitive aspect of translation discourse has a hierarchical structure consisting of two levels of cognitive discourse organization: cognitive-regulatory and cognitive-representative. Translation strategy is seen as a cognitive regulative that controls the organization and implementation of the translation discourse. The strategy directs the translator’s discourse creating activity which lies in the re-creation of the concept of the original text to integrate it into another language culture. Global strategies govern local strategies, which in turn determine the tactics and techniques and methods of translation. References Jaaskelainen, R. (1999). Tapping the process: an explorative study of cognitive and effective factors involved in translating. Joensuu: University of Joensuu Publications in Humanities. Krings H. P. (1986). Translation Problems and Translation Strategies of Advanced German Learners of French. Interlingual and Intercultural Communication. Tubingen: Gunter Narr, 263–275. Loescher W. (1991). Translation Performance, Translation Process and Translation Strategies. Tübingen: Gunter Narr. McElhanon, K. A. (2005) From Word to Scenario: The Influence of Linguistic Theories Upon Models of Translation. Journal of Translation, 1 (3), 29–67. Rosman, A. and Paula G. Rubel (2003). Are Kinship Terminologies and Kinship Concepts Translatable? In: Translating cultures : perspectives on translation and anthropology. (pp. 269–283). Paula G. Rubel and Abraham Rosman (Eds.). Oxford, N.Y. Андрієнко Т.П. Стратегії очуження й одомашнення в перекладі художнього дискурсу з англійської мови на українську: монографія. – К.: КиМУ, 2011. Andriyenko, T.P. (2011). Stratehiyi ochuzhennya y odomashnennya v perekladi khudozhn’oho dyskursu z anhliys’koyi movy na ukrayins’ku [Foreignizing and domestication strategies in translation of artistic discourse from English into Ukrainian]. Kyiv : KyMU. Балабін В. В. Сучасний американський військовий сленг як проблема перекладу : автореф. дис. на здобуття наук. ступеня канд. філол. наук: спец. 10.02.16 «Перекладознавство» / В.В. Балабін. К., 2002. Balabin, V. V. (2002) Suchasnyy amerykans’kyy viyskovyy slenh yak problema perekladu [Modern American Military Slang as a Problem of Translation]. Kyiv: Taras Shevchenko National University of Kyiv. Бєлова А. Д. Комунікативні стратегії і тактики: проблеми систематики / А. Д. Бєлова // Мовні і концептуальні картини світу : зб. наук. пр. – К.: КНУ імені Тараса Шевченка, 2004. – С. 11–16. Belova, A. D. (2004) Komunikatyvni stratehiyi i taktyky: problemy systematyky [Communication strategies and tactics: problems of taxonomy]. Movni i Kontseptualni Kartyny Svitu, 11-16. Дейк ван Т. А. Язык. Познание. Коммуникация / Дейк ван Т. А. ; [пер. с англ. ; cост. Петров В.В. ; под ред. Гарасимова]. – М. : Прогресс, 1989. – 310 c. Dijk, T. van (1989). Yazyk. Poznaniye. Kommunikatsiya [Language. Knowledge. Communiсation]. Moscow: Progress. Дьяконова Н.А. Функциональные доминанты текста как фактор выбора стратегии перевода : дис. ... канд. филол. наук : 10.02.20 / Наталья Анатольевна Дьяконова. – М., 2004. Djakonova, N.A. (2004) Funkcional’nye dominanty teksta kak faktor vybora strategii perevoda [Functional dominants of the text as a factor in the choice of the translation strategy]. Moscow. Кашкин В. Б. Сопоставительные исследования дискурса / В. Б. Кашкин // Концептуальное пространство языка. – Тамбов: ТГУ, 2005. – С. 337–353. Kashkin V.B. (2005). Sopostavitel’nye issledovanija diskursa [Comparative studies of discourse]. Konceptual’noe Prostranstvo Yazyka, 337–353. Карабан В. И. Сложные речевые единицы: прагматика английских асиндетических полипредикативных образований : [монография] / Карабан В. И. – К. : Вища школа, 1989. Karaban, V. I. (1989). Slozhnye Rechevye Yedinitsy: Pragmatika Angliyskikh Asindeticheskikh Polipredikativnykh Obrazovaniy [Complex Speech Act: Pragmatics of English Asynthetic Polypredicative Formations]. Kyiv: Vyshcha Shkola. Карасик В. И. О категориях дискурса / В. И. Карасик // Языковая личность: социолингвистические и эмотивные аспекты : сб. науч. тр. – Волгоград-Саратов : Перемена, 1998. – С. 185–197. Karasik, V. I. (1998) O Kategorijah Diskursa [On Discourse Categories]. In: Yazykovaja Lichnost: Sotsiolingvisticheskiye i Eemotivnye Aspekty. (pp. 185–197). VolgogradSaratov: Peremena. Комиссаров В. Н. Современное переводоведение: Учебное пособие / Вилен Наумович Комиссаров. – М.: ЭТС, 2004. Komissarov, V. N. (2004) Sovremennoye Perevodovedenye [Contemporary Translation Theory]. Moscow: ETS. Кубрякова Е. С. Части речи с когнитивной точки зрения / Е. С. Кубрякова. – М. : Инт языкознания РАН, 1997. Kubrjakova E. S.(1997) Chasti Rechi s Kognitivnoy Tochki Zreniya [Parts of Speech from a Cognitive Perspective]. Moscow: Institut Yazykoznaniya RAN Приходько А.М. Концепти і концептосистеми в когнітивно-дискурсивній парадигмі лінгвістики / Анатолій Миколайович Приходько – Запоріжжя: Прем’єр, 2008. Prykhodko, A. M. (2008). Kontsepty i kontseptosystemy v kohnityvno-dyskursyvniy paradyhmi linhvistyky [Concepts and concept systems in cognitive discourse paradigm of linguistics]. Zaporizhzhya: Premyer. Ревзина О. Г. Дискурс и дискурсивне формации / О. Г. Ревзина. // Критика и семиотика. – Вып. 8. – Новосибирск, 2005 – с. 66 – 78. – Режим доступу: http://www.philology.ru/linguistics1/revzina-05.htm. Revzina, O. G. (2005) Diskurs i diskursivne formatsii [Discourse and discursive formations]. Kritika i Semiotika, 66–78. Retrieved from http://www.philology.ru/ linguistics1/revzina-05.htm. Рудяков А. Н. Язык или почему люди говорят (опыт функционального определения естественного языка) / Рудяков А. Н. – К. : Грамота, 2004. Rudyakov, A. N. (2004). Yazyk ili Pochemu Lyudi Govoryat [Language, Or Why Do People Speak]. Kyiv: Gramota. Чередниченко О.І. Про мову і переклад / Олександр Іванович Чередниченко. – К.: Либідь, 2007. – 248 с. Cherednychenko, O. I. (2007). Pro Movu i Pereklad [On Language and Translation]. Kyiv: Lybid. Шевченко І.С. Когнітивно-прагматичні дослідження дискурсу / І.С. Шевченко // Дискурс як когнітивно-комунікативний феномен / під загальн. ред Шевченко І. С.: Монографія. – Харків: Константа, 2005. – C. 105–117. Shevchenko I.S. (2005). Kohnityvno-prahmatychni doslidzhennya dyskursu [Cognitivepragmatic discourse studies] Dyskurs yak Kohnityvno-Komunikatyvnyy Fenomen. Kharkiv: Konstanta. Шевченко О. Н. Языковая личность переводчика: На материале дискурса Б. В. Заходера / Ольга Николаевна Шевченко: Дис. ... канд. филол. наук: 10.02.19 : Волгоград, 2005. Shevchenko, O.N. (2005). Yazykovaja lichnost’ perevodchika: Na materiale diskursa B. V. Zahodera [Language personality of the translator: based on Boris Zakhoder’s discourse]. Volgograd. Шмігер Т. Історія українського перекладознавства ХХ сторіччя / Тарас Шмігер. – К.: Смолоскип, 2009. Shmiher, T. (2009). Istoriya Ukrayinskoho Perekladoznavstva XX Storichchya [History of Ukrainian Translation theory of the Twentieth Century]. Kyiv: Smoloskyp. Фролова І. Є. Стратегія конфронтації в англомовному дискурсі: Монографія / Ірина Євгенівна Фролова // Харків, 2009. Frolova, I. Ye. (2009). Stratehiya Konfrontatsiyi v Anhlomovnomu Dyskursi [The Strategy of Confrontation in the English Discourse]. Kharkiv. Фролова І. Є., Андрієнко Т. П. Стратегії спілкування та стратегії перекладу / Ірина Фролова, Тетяна Андрієнко // Переклад у наукових дослідженнях представників харківської школи: колективна монографія / за ред.: Л. М. Черноватого, О. А. Кальниченка, О. В. Ребрія. – Вінниця : Нова Книга, 2013, C. 211 – 232. Frolova, I. Ye., Andriyenko, T. P. (2013). Stratehiyi spilkuvannya ta stratehiyi perekladu [Communication strategies and strategies of translation]. In: Pereklad u naukovykh doslidzhennyakh predstavnykiv kharkivskoyi shkoly. (pp. 211 – 232). L. M. Chernovatyi, O. A. Kalnychenko, O. V. Rebriy, (Eds.). Vinnytsya: Nova Knyha. East European Journal of Psycholinguisti